ANALISIS GANTI KERUGIAN TERHADAP KORBAN SALAH TANGKAP - Ilham, Fajjrul Nur; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Investigators are at the forefront of an initial process of examining criminal cases, which then if the files are in accordance with the delegation of case files will proceed to the trial stage conducted by the prosecutor. In carrying out their duties, the Indonesian National Police or investigators must act fairly and wisely in determining the truth of a criminal case. One of the duties of the Indonesian National Police is to conduct an investigation. The investigation process is an examination mechanism in criminal cases that functions to seek sufficient information, as well as to find and collect valid evidence regarding the case and to find the suspect, this is stated in Article 1 Paragraph 2 of Law Number 8 of 1981 KUHAP. To be able to convict a defendant, there are at least two valid pieces of evidence. Evidence is regulated in Article 184 paragraph (1) of the Criminal Procedure Code, valid evidence is: a. witness testimony; b. expert testimony; c. letter; d. instruction; e. defendant's statement. But in reality, at this time there are many cases of wrongful arrests that occur, from this it can be concluded that the beginning of this wrong arrest case is in the investigation process carried out by police investigators to the role of judges to decide cases in court. This research has the aim of how the legal protection carried out by the state in terms of compensation for victims of wrongful arrests to get justice and their rights after a case of wrong arrest occurs